LEONARD TUCHILATU – UNUL DINTRE CEI MAI SUBTILI POEȚI ROMÂNI DIN BASARABIA - MÎRZA, bibliotecară, Filiala „O. Ghibu”, Tatiana (BIBLIOPOLIS, 2020)
The author describes the life and activity of the poet and prose writer Leonard Tuchilatu (1951-1975), born in the commune of Bursuceni, Sangerei district. The poet Leonard Tuchilatu will remain in Romanian literature a presence that left deep traces of his creation being truly one of the most subtile Romanian poets and thinkers. This can convince anyone who opens his books.